Nowa dyrektywa tytoniowa w świetle postanowień Konstytucji RP: [The new tobacco products directive in the light of Polish Constitutional Law] (Studia Prawnicze / The Legal Studies, 2014)
Celem niniejszego artykułu jest dokonanie oceny rozwiązań przewidzianych przez nową dyrektywę tytoniową w zakresie ich zgodności z Konstytucją. O tym że, nie jest to jedynie intelektualne ćwiczenie mogą świadczyć doświadczenia innych państw. Spory dotyczące konstytucyjności przepisów regulujących rynek wyrobów tytoniowych stały się bowiem w ciągu ostatniej dekady powszechnym zjawiskiem, zaś sądy konstytucyjne wielu państw miały już możliwość dokonania oceny różnych rozwiązań regulacyjnych, w tym i takich, które są przewidziane przez nową dyrektywę. Jest więc prawdopodobne, że również w Polsce może zostać podjęta próba zakwestionowania – w abstrakcyjnym trybie kontroli hierarchicznej zgodności norm – konstytucyjności ustawy implementującej postanowienia nowej dyrektywy. Wskazywać na to mogą krytyczne wypowiedzi władz różnych ogólnokrajowych organizacji pracodawców, a więc jednego z podmiotów uprawnionych do złożenia wniosku o zbadanie konstytucyjności aktu prawnego. Nie można również wykluczyć możliwości złożenia in casu skargi konstytucyjnej lub przedstawienia pytania prawnego. The article assesses the compatibility of the new Tobacco Products Directive (TPD) with the Polish Constitution. It concludes that although the Polish Constitutional Tribunal remains in principle competent to review acts of EU law (including directives if certain conditions are met), the scope of such a review is very limited and consists only of assessing whether EU institutions acted within scope of the competences transferred to them. The same holds true for domestic measures which merely implement directives. As a consequence, any review of the TPD provisions will be very restricted and can hardly lead to their inapplicability on the Polish territory.The article also assesses the compatibility with the Polish Constitution of the plain packaging requirement, which is not provided for, but only suggested by the TPD. In this context, it concludes that the Tribunal will be fully competent to review any national measure that introduces such a restriction. Although the outcome of such a review cannot be predicted with certainty, the article posits that there are good grounds to believe that the plain packaging requirement will be considered constitutional (i.e. in particular with respect to those provisions of the Constitution which protect property and freedom of economic activity).